Mechanical Behaviour of Polymeric Foam Core at Various Orientation Angles - M. R. M., Rejab; M. M., Noor; M. S. M., Sani; M. M., Rahman; K., Kadirgama (2009)
Polymeric foam is widely used as core materials in various applications such as cushioning, padding, insulating, structural use and buoyancy. This is because of its ability to provide high bending stiffness tied with lightweight in composite sandwich construction. The purpose of this paper is to present the behaviour of polyurethane (PU) foam, which is fabricated in various orientation angles. There were five different orientation angles have been studied i.e. 0o, 30o, 45o, 60o and 90o. Three mechanical tests were performed under tension, compression and shear loads to investigate the polyurethane foam behaviour. Electron microscope was used to capture the microstructure of the specimens before and after the tests. Comparisons have been made between different orientation angles in fracture modes and mechanical properties. Deformation and failure occur during foam crushing are discussed according to experimental evidence. Since the main application of foam materials are for energy absorption, foam response under considerable compression has been studied intensively. At angle of 90o, it permits more localised failure with high energy absorption and in contrary, 0o which posses the lowest of energy absorption. Energy absorption for PU foam material tends to increase when the orientation of angle is increased.